Long term follow-up of humoral and cellular response to mRNA-based vaccines for SARS-CoV-2 in patients with active multiple myeloma - Mancuso, Katia; Zamagni, Elena; Solli, Vincenza; Gabrielli, Liliana; Leone, Marta; Pantani, Lucia; Rocchi, Serena; Rizzello, Ilaria; Tacchetti, Paola; Ghibellini, Stefano; Favero, Emanuele; Ursi, Margherita; et al. (Frontiers in Oncology, 2023)
Long-term kinetics of antibody (Ab) and cell-mediated immune (CMI) response to full anti-SARS-CoV-2 vaccine schedule and booster doses in Multiple Myeloma (MM) patients remain unclear. We prospectively evaluated Ab and CMI response to mRNA vaccines in 103 SARS-CoV-2-naïve MM patients (median age 66, 1 median prior line of therapy) and 63 health-workers. Anti-S-RBD IgG (Elecsys®assay) were measured before vaccination and after 1 (T1), 3 (T3), 6 (T6), 9 (T9) and 12 (T12) months from second dose (D2) and 1 month after the introduction of the booster dose (T1D3). CMI response (IGRA test) was evaluated at T3 and T12. Fully vaccinated MM patients displayed high seropositivity rate (88.2%), but low CMI response (36.2%). At T6 the median serological titer was halved (p=0.0391) in MM patients and 35% reduced (p=0.0026) in controls. D3 (94 patients) increased the seroconversion rate to 99% in MM patients and the median IgG titer in both groups (up to 2500 U/mL), maintained at T12. 47% of MM patients displayed a positive CMI at T12 and double-negativity for humoral and CMI (9.6% at T3) decreased to 1%. Anti-S-RBD IgG level ≥346 U/mL showed 20-times higher probability of positive CMI response (OR 20.6, p<0.0001). Hematological response ≥CR and ongoing lenalidomide maintenance enhanced response to vaccination, hindered by proteasome inhibitors/anti-CD38 monoclonal antibodies. In conclusion, MM elicited excellent humoral, but insufficient cellular responses to anti-SARS-CoV-2 mRNA vaccines. Third dose improved immunogenicity renewal, even when undetectable after D2. Hematological response and ongoing treatment at vaccination were the main predictive factors of vaccine immunogenicity, emphasizing the role of vaccine response assessment to identify patients requiring salvage approaches.